Associations between systemic inflammation, nutritional status, and cardiometabolic diseases and risk factors among adults living in transitional rural communities in Ecuador - Irina Chis Ster; Monsermin Gualan; Luz-Marina Llangari-Arizo; Andrea Lopez; Natalia Romero-Sandoval; Philip J. Cooper (PLoS ONE, 2026)
Background Chronic low-grade systemic inflammation, as indicated by elevated high-sensitivity C-reactive protein (hs-CRP), has been implicated in the pathogenesis of cardiometabolic diseases. Less is known about the role of total immunoglobulin E (IgE), a marker of type 2 T helper cell-driven inflammation, in such outcomes. Information on the relevance of these markers in rural populations in transitional rural communities remains scarce, despite their growing burden of non-communicable diseases. Objectives This study examined the associations between two inflammatory markers—CRP and total IgE—and cardiometabolic risk factors and diseases in adults from transitional rural communities in coastal Ecuador. Methods We conducted a cross-sectional analysis of 931 adults from ten rural agricultural communities. Standardized questionnaires, anthropometric measurements, and fasting blood samples were used to collect data on sociodemographics, body composition, biochemical risk factors, and inflammatory markers (CRP and total IgE). Cardiometabolic outcomes included hypertension, type 2 diabetes, metabolic syndrome, and history of vascular disease. Multivariable regression models accounting for clustering at household and community levels and adjusted for age, sex, and their interaction were used to examine associations. Results Elevated CRP (≥3 mg/L) was prevalent (50.9%) and significantly associated with hypertension (adjusted odds ratio [aOR] 1.69, 95% CI: 1.19–2.39), type 2 diabetes (aOR 2.53, 95% CI: 1.77–3.64), and metabolic syndrome (aOR 3.24, 95% CI: 2.30–4.58). Elevated CRP was also strongly linked to multimorbidity (aOR for ≥3–4 vs. no conditions: 5.96, 95% CI: 3.52–10.08, P < 0.001), as well as insulin resistance, low high-density lipoprotein, high triglycerides, and multiple adiposity measures. CRP associations were attenuated after adjusting for body mass index, suggesting adiposity as a mediator. In contrast, elevated total IgE (≥140 IU/mL) did not seem to be associated with cardiometabolic diseases. Total IgE levels were higher in men and associated with short stature, illiteracy, and obesity. Conclusions Elevated CRP was strongly linked to cardiometabolic diseases and risk factors in this population, consistent with a model in which adiposity is a primary upstream driver of systemic inflammation. These findings highlight the importance of inflammation as a potential modifiable risk pathway and support the utility of CRP as a screening tool in low-resource transitional settings.